Analysis of Measurement Tidal Type of Musi River - Febriansyah Febriansyah; Erika Buchari; Edi Kadarsa (AIBPM Publisher, 2025)
Along the Musi River, there are transportation activities involving both passenger and cargo transport. However, all these activities are affected by the Musi River’s tidal fluctuations. Cargo transport on the Musi River is heavily dependent on the tidal conditions. The dimensions of the ships operating in the Musi River are determined by the river’s depth, which is influenced by these tidal changes. Consequently, the draft of the vessel that can operate is limited by the prevailing depth conditions of the river. This study aims to identify the highest and lowest tidal levels in the Musi River, determine the tidal pattern type, and forecast tidal conditions for December 2026. The methodology employed in this research is the Admiralty Method, which is based on observational data collected over 29 days, ensuring high accuracy in the results. From the research findings, the highest tide reached 551 cm, while the lowest tide recorded was 215 cm, resulting in a tidal range of 336 cm. The type of tidal pattern observed in the Musi River is classified as a mixed prevailing diurnal type, with a HHWL of 557.71 cm, a MSL of 364.5 cm, and a LLWL of 171.26 cm. Based on the tidal forecast for December 2026, the highest tide is projected at 511.1 cm, while the lowest is 219.3 cm, resulting in a tidal range of 291.9 cm. This research is anticipated to provide valuable insights into determining safe ship dimensions for navigation on the Musi River